Comparative evaluation of local storage and MinIO object storage for django applications in docker-based environments - Hendra Saputra; Faldi Faldi; Wawan Joko Pranoto (Institute of Computer Science (IOCS), 2026)
Media file management, such as documents and images, was an important aspect of Django-based web application development. Local storage was commonly used to store media files; however, it had limitations in terms of deployment portability, data management, and service continuity in containerized environments. Object storage emerged as an alternative approach by separating file storage from the application layer. This study compared the use of local storage and MinIO object storage in a Django application deployed using Docker containers. A comparative experimental method was employed by implementing both storage approaches on the same application under identical deployment conditions. The evaluation focused on file upload functionality, file accessibility, data persistence after container restart and redeployment, and deployment portability. The results indicated that both approaches successfully stored and provided access to media files. However, MinIO demonstrated advantages in data persistence, storage management, and deployment portability because media files were maintained independently from the application container. In contrast, local storage offered simpler implementation but required additional management during application migration or infrastructure changes. The findings suggested that MinIO object storage was more suitable for Django applications requiring flexible deployment and scalable file management in container-based environments.